Chemical attributes of a degraded soil after application of water treatment sludges - da Silva, E. T. (2005)
Mining is an activity that tends to degrade the environment. The restoration of mining areas, aims to accelerate and improve the succession process according to its future use. The objective of this work was to rehabilitate a soil degraded by tin mining activities in the Amazon Basin (Jamari National Forest, State of Rondonia) with the application of water treatment sludge (WTS), and verify the effect of Sludge on Values of pH (CaCl2 0.01 mol L-1), organic matter, P, Ca, Mg, K, H+Al, and soil micronutrient contents when Cultivated with native plants, legumes, and grass species. A factorial (3 x 5) experimental design was used to optimize the rehabilitation of these areas including three N rates (100, 200, and 300 mg N ka(-1) soil supplied by WTS), five plant species (grasses, legumes, and native plants), and two controls (degraded soil with no fertilizer and degraded soil fertilized with mineral fertilizers), with four replications. WTS increased pH values. The chemical products used to treat the water contributed, in greater extension, to increase soil Ca and Fe contents. The use of WTS as fertilizer proved viable, since it contains nutrients for plants; however, nitrogen Should not be used as a criterion to define the rate of Sludge application, because it is present at small amounts in the WTS.